أثر إستراتيجيات إدارة الصراع على الإبداع التنظيمي في المؤسسة - بالطيب, عيشة; بن قدور, نسيم; يعقوب, أسماء (University of eloued جامعة الوادي, 2019)
"تناولنا في هذه الدراسة موضوع أثر إستراتيجيات إدارة الصراع على الإبداع التنظيمي، دراسة حالة في مؤسسة مديرية توزيع الغاز والكهرباء بالوادي، وهدفنا إلى التعرف على وجهة نظر العاملين في المؤسسة، لطبيعة العلاقة بين إستراتيجيات إدارة الصراع والإبداع التنظيمي، ولتحقيق أهداف الدراسة استخدمنا إستبانة لجمع البيانات، وقد وزعت على عينة بلغ عددها (60) عامل، وتم استرجاع (45) إستبانة. حيث اعتمدنا في تحليل البيانات على المتوسط الحسابي، الانحراف المعياري، الارتباطات الخطية... وبعد تحليل الدراسة وظهور النتائج، فعلى المؤسسة أن تتخذ ببعض التوصيات وهي: ضرورة التخفيف من إستخدام إستراتيجية السيطرة واللجوء إلى استراتيجية التعاون، بل يجب المواجهة بين الأطراف وتفهم وجهات نظر بعضهم البعض والتحاور من أجل الوصول إلى حلول جذرية، الإستفادة من الإمكانيات الموجودة والمهارات المتاحة الأمر الذي ينهي القدرة الابداعية. ""Effect strategies Administration we ate in a this studing theme conflict on creativity Organiwational structure a study status in a Establishment directorate distribution gaz and electricity alwad and our goal to me ldentify on destination consideration staff in a enterprise of nature relationship between strategies administration conflict and creativity organizationl structure and to achieve goals studying we used ldentification to collect data the distributed on a sample d number (60)worker it was recovery (45) ldentification. Where we adopted in analysis data on analysis statistics descriptive and average my account and deviation standard and links the linear. After analysis studying and appearance results, qctual enterprise that take some recommendation which, necessity mitigation form strategy the control and asylum to me strategy coopert, but must be confrontation between the parties and understand their views of each other and dialogue in order to reach potholes, making use of the existing possibilities and the available skills will end the creativity. "
مذكرة ماستر ادارة اعمال
Keywords: إدارة الصراع، إستراتيجيات إدارة الصراع، الإبداع التنظيمي.; conflict management, conflict management strategies, organional careativity.